(untitled) (Third Sector Social Economic Review, 2019)
A materialist lifestyle seems to be an inseperable part of modern life for developed countries. People are spending money to acquire social status with power and prestige presented by money and property, to close individual flaws, to survive and to achieve self-esteem. Nowadays, people put material assets at the center of their lives. In this context, the purpose of this research is to examine the effect of the materialist tendencies of the students at the University of Cumhuriyet on the impulsive buying behavior. Within the scope of the research, the ""Materialism Scale"" developed by Ger and Belk (1996) and the impulsive purchase scale developed by Rook and Fisher (1995) were used in the study. As a result of the regression analysis, it was concluded that non-generosity and jealousy factors had a significant and positive effect on the impulsive purchasing behavior, but no significant effect of the retention factor. In addition, t-test and variance analysis were conducted to determine whether the materialist tendencies and impulsive buying behaviors of the students varied according to demographic characteristics. According to the results, while the size of non-generosity varied according to gender, income, type of teaching and grade of class being read, the instant buying behavior varied according to gender, income and type of education.